2021
DOI: 10.7150/jca.50108
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy of Involved Field versus Elective Lymph Node in Patients with Operable Esophageal Squamous Cell Cancer: A Single Institution Prospective Randomized Controlled Study

Abstract: Background: To evaluate locoregional failure and its impact on survival by comparing involved field irradiation (IFI) with elective lymph node irradiation (ENI) for patients with esophageal squamous cell cancer who underwent post-operative radiotherapy. Methods and Materials: The enrolled patients were randomized allocated to IFI or ENI group. CTV of IFI was generated according to pre-operative primary tumor location and post-operative pathological characters and positive LNs regions. CTV of ENI was generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Our preliminary results demonstrated that the survival outcomes did not differ signi cantly, consistent with the results of other studies [27]. Before 2021, our center mainly adopted ENI irradiation (168/208 patients, 80.0%).…”
Section: Discussionsupporting
confidence: 89%
“…Our preliminary results demonstrated that the survival outcomes did not differ signi cantly, consistent with the results of other studies [27]. Before 2021, our center mainly adopted ENI irradiation (168/208 patients, 80.0%).…”
Section: Discussionsupporting
confidence: 89%
“…Li et al (11) analyzed 110 esophageal cancer patients (including 56 in the ENI group and 54 in the IFI group), and found that the IFI group had significantly lower incidence of grade ≥2 radiation pneumonitis and radiation esophagitis compared to the ENI group (12.9% vs. 26.8%, P=0.011; 20.4% vs. 37.5%, P=0.001). Liu et al (12) found that the incidence of acute radiation pneumonitis (p=0.005) and hematologic toxicity (p=0.029) was significantly higher in the ENI group compared to the IFI group. Cheng et al ( 13) also observed that the incidence of grade ≥3 acute esophagitis and pneumonitis was significantly lower in the IFI group compared to the ENI group.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. ( 12 ) found that the incidence of acute radiation pneumonitis (p=0.005) and hematologic toxicity (p=0.029) was significantly higher in the ENI group compared to the IFI group. Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is unwise to exert excessive radiation dosages in the therapy process to obtain the desirable radiotherapeutic efficacy, as blindly increasing the radiation dosage can not increase the efficacy of radiotherapy but aggravate the injury of normal tissue. 11,12 The employment of radiosensitizers may be a proper strategy to overcome the radiation resistance and achieve relatively safe and low-dosed radiation therapeutics. 13 The combination treatment is also regarded as an effective solution to optimize therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%